Pengaruh Beban Kerja Fisik Terhadap Keluhan Mukuloskeletal Pada Tenaga Kerja Bongkar Muat (TKBM) di Pelabuhan Yos Sudarso Ambon - Mamuly, Wilma Fransisca; Embuai, Yowan (Jurnal Ners, 2024)
The work of workers, in this case loading and unloading workers, has a high risk of occupational diseases which can reduce worker productivity. One of the diseases that may arise due to work is musculoskeletal complaints, namely complaints in the skeletal muscles which are felt in the muscles that attach to the bones and produce excessive movement force. The aim of this research is to determine the effect of physical workload. against muculoskeletal complaints in loading and unloading workers (TKBM). This research is a quantitative research with a cross-sectional approach. This type of research is correlation analytic with a cross-sectional design. It is necessary to carry out research on TKBM workers on ship workers so that they can reduce the capacity/load of excessive amounts of goods, correct wrong/incorrect working positions, and reduce the duration of work that is too long with physical activities carried out so as to reduce the risk that can trigger musculoskeletal complaints. . The research results show that there is an influence between work load, work attitude, work duration of loading and unloading workers at Yos Sudarso Ambon Port and musculoskeletal complaints with a P value of 0.000. Suggestions: TKBM workers are expected to be able to pay attention to the weight of the load that will be lifted, where workers need to adjust the load to body capacity, pay attention to odd working attitudes, pay attention to the wrong working position when lifting the load so as not to experience fatigue and muscle injury, and pay attention. time or duration of work in a day not to overwork the work force, paying attention to the time to rest, by making body movements to feel more comfortable before continuing work activities.